The Multifunctionality of the Grammatical Lām: New Insights from Contemporary Linguistic Studies - Mahmud Hambali; Fachrul Ghazi; Syaripudin Basyar (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
The Arabic letter “Lām (ل)” is considered one of the most significant and versatile particles in Arabic grammar due to its wide range of syntactic and semantic functions. Its meanings vary among ownership, specification, causation, emphasis, and oath, making it one of the most complex yet richest particles in the Arabic linguistic system. This study aims to identify the types, functions, and meanings of Lām to facilitate understanding among learners and teachers of Arabic and to promote accurate usage in interpreting Qur’anic, prophetic, and rhetorical texts.The research adopts a library-based qualitative method, collecting data from classical grammatical references such as Mughnī al-Labīb by Ibn Hishām, al-Jin al-Dānī by al-Murādī, and modern linguistic works addressing the semantics of particles. The findings show that Lām is divided into operative (ʿāmilah) types—such as the genitive Lām, Lām of command, and Lām of purpose—and non-operative (ghayr ʿāmilah) types—such as Lām of initiation, Lām al-muzahlaqah, Lām al-fāriqah, and others. Its function shifts according to sentence structure and context, expressing possession, causation, emphasis, or oath. This research highlights the precision and richness of Arabic syntax and underscores Lām as a key element in understanding grammatical relationships and subtle meanings within Arabic discourse.